The value of nothing how to reshape market society and redefine democracy - Patel, Raj (Portobello Books Ltd., 2011)
Patel shows how our faith in prices as a way of valuing the world is misplaced and reveals that our current crisis is not simply the result of too much of the wrong kind of economics but rather the larger failure of a democratically bankrupt political system. The solution he offers: discover democratic ways in which people, and not simply governments, can play a crucial role in deciding how we might share our world and its resources in common.